The Novelty Issues In The Agroindustrial Research - .http://172.17.5.57/index.php/jurnaltin/ Sukardi (Jurnal Teknologi Industri Pertanian, 2009)
This article discusses some issues of novelty in the agroindustrial research faced by graduate students in the department of Agroindustrial Technology.  It proposes three types of novelty that students may select for their dissertation research, i.e., the novelty type of invention, improvement, and refutation.  These types of novelty are categorized based on some fundamentals background taken from the works of some distinguished scientists and scholars from the early stage of science and technology development to the modern one.  The article argues that if the novelty issues in the agroindustrial research can be perceived, the findings of the research will be the sources of agroindustrial development.  The conjectures in this article are open for discussions, critiques, and objections simply for the sake of improvement of our agroindustry.Keywords: novelty, invention, innovation, refutation.